PENGARUH SELF ASSESSMENT SYSTEM, E-COMMERCE DAN KETERBUKAAN AKSES INFORMASI REKENING BANK TERHADAP NIAT MELAKUKAN PENGHINDARAN PAJAK - Dewi Kusuma Wardani; Nila Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to examine the effect of self assessment system, e-commerce, and open access to bank account information against tax avoidance intentions.The data used is primary. Multiple regression analysis is the analytical method used. The sampling technique used in this study was the purpose sampling method and obtained 70 data samples.The regression test results show that the self assessment system has a positive effect on the intention to do tax avoidance. Whereas e-commerce and open access to bank account information have no effect on tax avoidance intentions.